When Is There Enough Data to Create a Global Statistic ? - Mahler, Daniel Gerszon; Serajuddin, Umar; Maeda, Hiroko (Washington, DC: World Bank, 2022)
To monitor progress toward global goals such as the Sustainable Development Goals, global statistics are needed. Yet cross-country data sets are rarely truly global, creating a trade-off for producers of global statistics: the lower is the data coverage threshold for disseminating global statistics, the more statistics can be made available, but the lower is the accuracy of these statistics. This paper quantifies the availability-accuracy trade-off by running more than 10 million simulations on the World Development Indicators. It shows that if the fraction of the world’s population for which data are lacking is x, then the global value will on expectation be off by 0.37*x standard deviation, and it could be off by as much as x standard deviations. The paper shows the robustness of this result to various assumptions and provides recommendations on when there is enough data to create global statistics. Although the decision will be context specific, in a baseline scenario, it is suggested not to create global statistics when there are data for less than half of the world’s population.